Program Kemitraan Masyarakat (PKM) Perkumpulan Petani Pemakai Air (P3A) Aga di Kelurahan Taratara Satu Kota Tomohon : Community Partnership Program (PKM) for Water User Farmers (P3A) Aga in Taratara Satu Sub-district, Tomohon City (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Taratara Satu Sub-district is one of the agricultural / rice fields located in Tomohon City, North Sulawesi Province with a fairly rapid population growth rate and economic development.  The expansion of new land for agriculture/rice fields causes a shortage of irrigation water and poor governance of irrigation water use due to the absence of a well-organized water network in the village. The implementation of the Community Partnership Program begins with a direct survey to the location to find out what problems exist. It was found that not all rice fields were watered because at a certain time there was a water drought which greatly affected the productivity of agricultural products/rice fields. From the existing problems, socialization materials related to Operation and Maintenance on the irrigation system in Taratara Satu Sub-district were prepared, because many channels are no longer functioning. Providing an understanding of how to plan a good irrigation system, how to operate and maintain the irrigation system, who is responsible for the functioning of irrigation. The same thing is not done in the irrigation system. Suitable and environmentally friendly methods were also introduced to strengthen drought response communities, especially for agricultural land/rice fields.